Seed dispersal and germination of Cryptocarya moschata Nees & Martius Ex Nees, Ocotea catharinensis Mez and Endlicheria paniculata (Sprengel) Macbride (Lauraceae) - Moraes, Pedro Luis Rodrigues de [UNESP]; Paoli, Adelita Aparecida Sartori [UNESP] (Inst Tecnologia Parana, 1995)
Data of seed dispersal and germination of the studied species are presented, comparing both observations from the wild and nursery. Fruits were collected from Carlos Botelho State Park (24 degrees 44' to 24 degrees 03'S, 47 degrees 46' to 48 degrees 10'W), south of São Paulo State, Brazil. O. catharinensis had low germination percentage, both in the wild and in nursery, and did not tolerate seed storage at low temperature. In nursery, diaspores with removed mesocarp of E. paniculata presented greater germination than those in entire fruits. The high levels of seedling mortality beneath mother-trees of C. moschata, when in comparison to those observed to established seedlings from diaspores dispersed by muriquis (Brachyteles arachnoides E. Geoffroy 1806, Cebidae, Primates), allied to the absence of juveniles in the understory, are in accord with the escape model of Janzen-Connel. In nursery, diaspores of C. moschata dispersed by the primates had greater germination, in smaller time, than those collected from mother-trees.
Keywords: seed dispersal; seed germination; Cryptocarya moschata; Ocotea catharinensis; Endlicheria paniculata; Lauraceae